plese solve it as soon as possible

Asked by jayantkaushik | 7th Sep, 2009, 06:18: PM

Expert Answer:

f(x) = 6x3 - 11x2 + kx - 20

f(4/3) = 0.

6(4/3)3 - 11(4/3)2 + k(4/3) - 20 = 0

6(64/27) - 11(16/9) + k(4/3) - 20 = 0

k(4/3) = 20(27)/27 + 11(3)(16/27) - 6(64/27)

k(4/3) = [20(27) + 11(3)(16) - 6(64)]/27

k = 19.

Regards,

Team,

TopperLearning.

 

 

Answered by  | 7th Sep, 2009, 07:08: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.